Perceived Herding Behavior and Experienced Regret on Crypto Asset’s Investment Decisions by Millennials - Elyza Putri Rosmiwilujeng; Made Dudy Satyawan; Halil Paino (AKRUAL: JURNAL AKUNTANSI, 2024)
ntroduction/Main Objectives: This research aims to determine the effect of herding behaviour andexperienced regret on millennials' decisions to invest in crypto assets. In addition, this researchwould explain the investment decisions of crypto assets in urban communities in the Surabaya andSidoarjo areas. Background Problems: The number of crypto asset enthusiasts had increasedsignificantly over the past few years. Commodity Futures Trading Supervisory Agency (BadanPengawas Perdagangan Berjangka Komoditi/BAPPEBTI) noted that crypto investors in Indonesiahad reached 17.25 million people in April 2023. Under these conditions, investors' behaviour can beinfluenced by psychological and emotional factors such as herding behaviour and experiencedregret. Research Methods: The research method used a survey method with a sample of studentsand employees domiciled in the urban areas of Surabaya and Sidoarjo. The analysis technique usedin this research was multiple linear regression analysis using SPSS version 26 software.Finding/Results: The research results showed that herding behaviour and experienced regret had apartially positive effected on millennials' investment decisions in crypto assets. Conclusion: Thenovelty of this research was to explain the differences in crypto asset investment decisions betweenstudents and employees